2019
DOI: 10.1111/bph.14686
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of STAT3 activation mediated by toll‐like receptor 4 attenuates angiotensin II‐induced renal fibrosis and dysfunction

Abstract: Background and Purpose Hypertension adversely affects the kidney and is the second leading cause of kidney failure. Overproduction of angiotensin II greatly contributes to the progression of hypertensive kidney disease. Angiotensin II has recently been shown to activate STAT3 in cardiovascular cells. However, the underlying mechanisms of STAT3 activation by angiotensin II and downstream functional consequences in the kidneys are not fully understood. Experimental Approach C57BL/6 mice were treated with angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Many studies have shown that inhibition of the STAT3 signaling pathway reduces renal inflammatory response and renal interstitial fibrosis. 43 , 44 , 45 Our in vivo experiments demonstrated that although high-intensity exercise had no effect on renal EMT, it significantly activated STAT3. In vitro experiments then confirmed that irisin upregulates p-STAT3 and activates the STAT3 pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have shown that inhibition of the STAT3 signaling pathway reduces renal inflammatory response and renal interstitial fibrosis. 43 , 44 , 45 Our in vivo experiments demonstrated that although high-intensity exercise had no effect on renal EMT, it significantly activated STAT3. In vitro experiments then confirmed that irisin upregulates p-STAT3 and activates the STAT3 pathway.…”
Section: Discussionmentioning
confidence: 69%
“…We have recently shown that Ang II activates STAT3 in renal epithelial cells to increase the expression of fibrotic factors COL-4 and TGF-β1. 12 Our present study demonstrates that a possible mechanism of increased STAT3 activity may be FGFR1. We show that inhibiting FGFR1 by ADZ4547 or reducing its expression supresses Ang II–induced STAT3 Y705 phosphorylation and downstream fibrotic factor expression.…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, the roles of IL-6 were reported in several kidney diseases and targeting IL-6 could protect against renal fibrosis by suppressing STAT3 activation [ 34 , 35 ]. Some studies have found that STAT3 signaling can control the EMT of renal tubular epithelial cells during renal injury, and dysregulated STAT3 may lead to renal disease, including inflammation and fibrosis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%